Functional hierarchy and algorithms for managing complex technical systems - Піскун, Сергій Жанович; Хорошко, Володимир Олексійович; Хохлачова, Юлія Євгенівна (Ukrainian Information Security Research Journal, 2013)
Based on the research, we suggest the following sequence of actions in the synthesis of new or improve the existing organization of the system: determination of elements (subsystems) performance, grouping items subsystems for specific tasks performed, and analysis tasks of planning, management and control in groups, identification based on the analysis of the number of controls the formation of the structure of individual levels as models of technical systems. Thus, the combination of purely organizational practices and management of technical systems allows the development of algorithms for generalized type whose use should be recommended in complex systems. Obviously, in each case, binding to the actual conditions of the system based on a detailed analysis of each application subsystem. The aim is to develop recommendations for the synthesis of new or upgrading existing organization functioning of the systems, including security systems, as well as an algorithm for the management of the generic type of technical systems of varying complexity and purpose.